Critical shortfalls in vape liquid traceability - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
THE incidence of acute nicotine poisoning among children due to vaping is a stark reflection of a far-reaching issue: the critical lack of much-needed regulation. This distressing concern calls for immediate, comprehensive attention.